Membrane Bioreactor Technology: The Effect of Membrane Filtration on Biogas Potential of the Excess Sludge - Magdalena Zielińska; Katarzyna Bernat; Wioleta Mikucka (Membranes, 2020)
Although the membrane bioreactor technology is gaining increasing interest because of high efficiency of wastewater treatment and reuse, data on the anaerobic transformations of retentate are scarce and divergent. The effects of transmembrane pressure (TMP) in microfiltration (MF) and ultrafiltration (UF) on the pollutant rejection, susceptibility of ceramic membrane to fouling, hydraulic parameters of membrane module, and biogas productivity of retentate were determined. Irrespective of the membrane cut-off and TMP (0.2–0.4 MPa), 97.4 ± 0.7% of COD (chemical oxygen demand), 89.0 ± 4.1% of total nitrogen, and 61.4 ± 0.5% of total phosphorus were removed from municipal wastewater and the permeates can be reused for irrigation. Despite smaller pore diameter, UF membrane was more hydraulically efficient. MF membrane had 1.4–4.6 times higher filtration resistances than UF membrane. In MF and UF, an increase in TMP resulted in an increase in permeate flux. Despite complete retention of suspended solids, strong shearing forces in the membrane installation changed the kinetics of biogas production from retentate in comparison to the kinetics obtained when excess sludge from a secondary clarifier was anaerobically processed. MF retentates had 1.15 to 1.28 times lower cumulative biogas production than the excess sludge. Processing of MF and UF retentates resulted in about 60% elongation of period in which 90% of the cumulative biogas production was achieved.